Conducting polymers-based nanocomposites: Innovative materials for waste water treatment and energy storage. (2022) - Shahabuddin, Syed; Gaur, Rama; Mukherjee, Nandini; Chandra, Prakash; Khanam, Rashmin
Abstract: Over the years, the concept of intrinsically conducting polymers (ICP) endures to intrigue the scientific community owing to its unique properties. ICP is an organic macromolecule that integrates both the conventional polymers and metal properties into one system. The current research article discusses the simplistic methodology for the synthesis of metal oxide doped polyaniline (PANI) nanocomposites via in-situ oxidative polymerization procedure for photocatalysis and supercapacitor application. The synthesised materials are usually characterised by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and BET analysis. The photocatalytic performance of the nanocomposites is usually evaluated by monitoring the degradation of model dyes under UV irradiations whereas the supercapacitor performance is evaluated by fabricating electrodes to analyse the electrochemical efficiencies. The reported literature indicates that the conducting polymers doped nanocomposites revealed better photocatalytic and capacitance efficiencies as compared to bare PANI. Enhanced photocatalytic and electroanalytical performance, simple method for synthesis and cheaper cost of production made these materials to be exploited as potential candidates for efficient energy storage and waste water treatment.